Parenting Conflicts in Young Adults with Adverse Childhood Experiences: Family Conflict Theory Analysis - Diah Ayu Septiyani; Ika Febrian Kristiana (Green Publisher, 2025)
This study examined childhood trauma in young adults by parental conflict. The young adult phase is a very important transition in which from adolescence to independence as an adult related to traumatic experiences resulting from past parenting patterns. Researchers using family conflict theory aim to explore and analysis the contribution of adverse childhood experiences to parenting conflict in young adults. Using systematic literature review and the PRISMA method by reviewing research articles published from 2015-2025, the keywords used were